Association between maladaptive sleep hygiene behaviors and sleep quality in the general population - Sancho-Domingo Clara; Carballo José Luis; Coloma-Carmona Ainhoa; Rodríguez-Marín Jesús (Psihologija, 2020)
Prevalence of sleep problems has grown globally in recent years and sleep hygiene recommendations have shown inconsistent results. This study aims to analyze the quality of sleep in a non-clinical population and its association with maladaptive sleep hygiene. A total of 465 participants, with median age of 35 years (Interquartile range – IQR = 28–44), completed the Sleep Hygiene Practices Scale (SHPS) and the Pittsburgh Sleep Quality Index (PSQI). Sample was divided into good quality sleepers (GQS; 52.7%, n = 245) and poor quality sleepers (PQS; 47.3%, n = 220). Comparison tests showed PQS had significant higher scores on SHPS (M = 61; IQR = 55–68, p < .01) compared with GQS (M = 68; IQR = 62–74). A logistic regression model indicated that only cognitive-arousal behaviors and inconsistent bedtimes were significant to classify poor sleep (R2 = .35; p < .01). In conclusion, poor sleep quality is common among healthy individuals and strongly associated with pre-sleep cognitive activity. This suggests that interventions aiming to improve sleep quality should consider strategies that would retract attention from concerns and worries at bedtime.